Atividade das enzimas purinérgicas e o uso de nanocápsulas de óleo de romã e silibinina no melanoma cutâneo - Cabral, Fernanda Licker (2022)
Cancer is a multifactorial disease resulting from mutations in specific genes that cause cell hyperproliferation. Currently, the most prevalent type of cancer is skin cancer, and its most aggressive subtype is melanoma. The rapid progression of the tumor is associated with the development of inflammation in the tumor microenvironment, which presents an immunosuppressive profile. During the inflammatory process, the purinergic signaling system plays an important role in modulating inflammatory and immune responses. E-NTPDase, E-5'- nucleotidase, and E-ADA ectoenzymes control the levels of extracellular biomolecules ATP, ADP, AMP, and adenosine. Such molecules participate in various physiological and pathological processes, including cell growth, apoptosis, cell proliferation, and angiogenesis. Melanoma, in turn, is highly heterogeneous, making it difficult for the immune system to recognize it and the efficiency of existing therapies. In this sense, phytochemicals such as pomegranate oil (OR) and silibinin (SB) can act in several signaling pathways and help fight cancer. In addition, encapsulating these bioactive compounds allows greater bioavailability and stability to these compounds, which may improve their effects. Thus, this work aimed to investigate the antitumor effect of the co-encapsulation of OR and SB in cell culture (B16F10 from murine melanoma and L929 from healthy murine fibroblasts) and to evaluate the activity of purinergic enzymes in an experimental model of cell-dependent melanoma induction pathway. The OR and SB nanocapsules showed physicochemical characteristics compatible with nanostructured systems. The in vitro results showed that free SB and OR had little effect on the viability and proliferation of B16F10 cells. However, the nanocapsules (NC-SB and NC-OR) enhanced the cytotoxic effects on these cells and conferred a certain type of protection to healthy cells. Co-encapsulation of SB and OR (NC-PO-SB) demonstrated an antitumor effect through marked reduction of cell viability and proliferation (P<0.001), migration, adhesion, and colony formation (P<0.001), increase in cells in the G1/G0 phases of the cell cycle (P<0.001), increased DNA damage (P<0.05) and NO levels (P<0.001). In the in vivo study, by inducing B16F10 cells in C57BL/6 mice by intraperitoneal and subcutaneous routes, we observed a reduction in lymphocyte count and an increase in the number of neutrophils, and increasing the neutrophil/lymphocyte ratio in the induced groups compared to the control (P<0.05). In the subcutaneous (SC) route, there was a decrease in the activities of E-NTPDase and E-ADA in lymphocytes isolated from blood and thymus and an increase in both activities in the spleen when compared to the control. In the intraperitoneal (IP) route, the lymphocytes isolated from the blood did not show different activities from the control. Thymus and spleen lymphocytes and intraperitoneal cells had reduced enzymatic activities compared to the control. We observed this organomegaly in the spleen, with an increase in white pulp and an increase in arginase enzyme activity (P<0.05). In general, blood and thymus lymphocytes are most activated in the SC pathway, which requires more of the vasculature, and spleen lymphocytes and intraperitoneal cells correlated with the IP pathway due to proximity to the tumor. In both pathways, lymphocytes direct the activities of ectoenzymes to increase the P2 signal, pro-inflammatory and antitumor. Considering the results presented, we suggest that the suspension of NC-PO-SB could be considered a therapy for melanoma and that ectoenzymes are therapeutic targets.